Positive Psychology in Spain: A portrait of a vigorous field of research - Hervás, Gonzalo (Anales de Psicología / Annals of Psychology, 2016)
<span style="font-family: ’Garamond’,serif; font-size: 8pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-fareast-language: AR-SA; mso-bidi-font-size: 10.0pt; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Positive Psychology has been alive for almost two decades and it is a good moment to take stock and, most importantly, present a set of studies that allow us to identify trends, interests, methodologies and results that are being generated within our borders. This monograph is thus an invitation to the reader, either researcher or professional, to explore this territory and use this as a starting point for further investigation in the Positive Psychology literature